Protein losses caused by peritoneal dialysis and influencing factors - TANG Xing-ming; HU Jie-ping; DENG Hui-zhao; LIN Jian; ZHENG Wei-ping; ZOU Zhao-hui (Linchuang shenzangbing zazhi)
Objective To investigate the components of protein in peritoneal dialysate and explore the risk factors causing the protein losses in the peritoneal dialysis patients in Donghua hospital. Methods122 uremic patients( 79 males and 43 females) undergoing continuous ambulatory peritoneal dialysis( CAPD)were enrolled and assigned into high protein losses group( HP) and low protein losses group( LP) according the median losses of protein in dialysate from March 1,2015 to Feb. 28,2016. The amount and component of the protein in dialysate were accessed by the immunoturbidimetry and electrophoresis,and the demographic data and clinical data were collected to analyze the difference between the two groups. The logistic regression was applied to disclose the risk factors of the protein losses via dialysate. Results The median of protein losses in CAPD dialysis patients was 4. 18 g/24 h,the major component was albumin( 0. 36 g/L),the other components were transferrin,IgG and Ig A,and all of them were more eliminated in the dialysate of patients in HP group( P < 0. 001). Furthermore,the patients in HP group showed lower serum albumin( 37. 33 ± 3. 85 vs.39. 05 ± 3. 88 g/L,P < 0. 001) and higher rate with high transport status( 59. 0% vs. 34. 4%,P =0. 006),and high peritoneal transport was risk factors of high protein losses by dialysate( OR 3. 08,95%CI 1. 41-6. 75). Conclusions CAPD patients may lose substantial amount of protein by dialysis solution,the major components was albumin,and high peritoneal transport was risk factors of high protein losses by dialysate.